Marine resource management and conservation through sasi customary law: A case study of Namatota Village, Kaimana District, West Papua - Andarifka Daffa Aryabima (Privietlab, 2026)
The management of marine resources in Indonesia’s coastal areas increasingly requires approaches that integrate ecological sustainability with sociocultural contexts. One form of local wisdom that continues to be practiced in eastern Indonesia is sasi, a customary law system that regulates the utilization of natural resources through temporary prohibitions. This study aims to analyze the closing of sasi adat as a mechanism for managing and sustaining marine resources through a case study in Namatota, Kaimana Regency, West Papua. This research employs a descriptive qualitative approach using field observations and a literature review. The findings indicate that tutup sasi adat functions not only as an ecological conservation instrument by providing recovery periods for marine ecosystems but also as a social control mechanism that strengthens community compliance with customary law. The integration of tutup sasi practices with the Sasi Gam Festival further reinforces cultural transmission, documentation, and community awareness of sustainable resource management. The study concludes that closing of sasi adat represents an effective and adaptive form of customary marine resource management rooted in local wisdom, contributing to environmental sustainability and local food security. Strengthening customary institutions and aligning customary practices with formal governance frameworks are essential to ensure the continuity of tutup sasi amid contemporary socioeconomic challenges.